Employment protection and temporary work agencies - Florian Baumann; Mario Mechtel; Nikolai Stähler (Deutsche Bundesbank, 2008)
Employers who use temporary agency staff in contrast to regular staff are not affected by employment protection regulations when terminating a job. Therefore, services provided by temporary work agencies may be seen as a substitute for regular employment. In this paper, we analyze the effects of employment protection on the size of the temporary work agency sector in a model of equilibrium unemployment. We find that higher firing costs may even reduce temporary work agency employment if agencies themselves are subject to employment protection, a consideration which distinguishes our results from those for fixed-term employment arrangements.
Keywords: J68; J65; J64; J30; 330; employment protection; temporary work agencies; search and matching models; unemployment; Kündigungsschutz; Wirtschaftspolitische Wirkungsanalyse; Leiharbeit; Theorie der Arbeitslosigkeit; Arbeitsuche; Matching; Theorie